منهج التفسير العرفاني في الاستعارات القرآنية: Cognitive Exegetical Trend in the Qur’anic Metaphors - Dr. Shakeel Ahmad; Dr. Musaab Iftikhar Durrani (Al Manhal Research Journal, 2022)
One of the most prominent characteristics of Quranic metaphors is that it is based on the mystical approach that works to study the movement of the mind in interacting with things in order to understand them, and how the human mind deals with the various metaphorical meanings revealed in the Holy Qur’an. This article sheds light on the mystical approach through which we can look at the work of the mind in understanding metaphorical pictures, and how to form the conceptual structure of people. Therefore, it was necessary to study this approach, which confirms the divine miracle in the creation of the human mind in order to comprehend the meanings of the Holy Quran, and to show how the metaphorical pictures in the Quran came, taking into account the nature and capabilities of the human mind. The Holy Quran collected all the elements of building an image such as sound, color, movement, events, and then used them to explain and clarify those things that are not seen with naked eye, to be embodied in the form of material things close to people’s understanding. We find that this process is repeated in all metaphorical pictures, as the Quranic text relied on depiction in its statement, but each image had its own merits.